Moral distress and burnout in internal medicine residents - Sajjadi, Sharareh; Norena, Monica; Wong, Hubert; Dodek, Peter (Canadian Medical Education Journal, 2017)
Background: Residents frequently encounter situations in their workplace that may induce moral distress or burnout. The objective of this study was to measure overall and rotation-specific moral distress and burnout in medical residents, and the relationship between demographics and moral distress and burnout. Methods: The revised Moral Distress Scale and the Maslach Burnout Inventory (Human Service version) were administered to Internal Medicine residents in the 2013-2014 academic year at the University of British Columbia. Results: Of the 88 residents, 45 completed the surveys. Participants (mean age 30+/-3; 46% male) reported a median moral distress score (interquartile range) of 77 (50-96). Twenty-six percent of residents had considered quitting because of moral distress, 21% had a high level of burnout, and only 5% had a low level of burnout. Moral distress scores were highest during Intensive Care Unit (ICU) and Clinical Teaching Unit (CTU) rotations, and lowest during elective rotations (p<0.0001). Women reported higher emotional exhaustion. Moral distress was associated with depersonalization (p=0.01), and both moral distress and burnout were associated with intention to leave the job. Conclusion: Internal Medicine residents report moral distress that is greatest during ICU and CTU rotations, and is associated with burnout and intention to leave the job.